2021
DOI: 10.7189/jogh.11.17001
|View full text |Cite
|
Sign up to set email alerts
|

Physical trauma and injury: A multi-center study comparing local residents and refugees in Lebanon

Abstract: Background Refugees are susceptible to various types of injury mechanisms associated with their dire living conditions and settlements. This study aims to compare and characterize the emergency department admissions due to physical trauma and injuries among local residents and refugees in greater Beirut. Methods This epidemiological study analyzes injury incidence and characteristics of patients presenting to Emergency Departments of 5 sentinel hospitals between 2017 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This study identified 397 patients who sustained occupational injuries while working for a construction income and were covered by Suva insurance, the Swiss Accident Insurance Fund. Consistent with previous studies, our research shows a predominance of male patients [ 37 , 38 ], and is in accordance with statistics showing that persons suffering from these types of injuries are males in 98% of the cases [ 37 ]. This is not surprising, considering that males, due to the nature of the job, are more frequently employed in high-risk sectors (e.g., construction industries and manufacturing) compared to females [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study identified 397 patients who sustained occupational injuries while working for a construction income and were covered by Suva insurance, the Swiss Accident Insurance Fund. Consistent with previous studies, our research shows a predominance of male patients [ 37 , 38 ], and is in accordance with statistics showing that persons suffering from these types of injuries are males in 98% of the cases [ 37 ]. This is not surprising, considering that males, due to the nature of the job, are more frequently employed in high-risk sectors (e.g., construction industries and manufacturing) compared to females [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Considering the severity of the injuries, our data show that the proportion of severe injuries is relatively low and comparable to that previously reported [ 38 ]. Indeed, only 9.8% of the patients had to be transferred by ambulance, whereas 79.3% were walk-in patients.…”
Section: Discussionsupporting
confidence: 91%
“…Al-Hajj et al [59] examined injured patients presenting to the ED and found that almost 90% of Lebanese patients sought care at private hospitals, as compared to only 52% of refugees (p-value < 0.001). According to the authors, a reason for this difference is that refugees are frequently unable to pay for medical care, therefore they are obliged to go to public hospitals or other facilities sponsored by local nongovernmental organizations (NGOs) or the United Nations High Commissioner for Refugees (UNHCR).…”
Section: Modalities Of Access and Utilization Of The Edmentioning
confidence: 99%
“…The current series further highlights that malnutrition, lack of quality education, poor physical and mental health, and extreme poverty have long- term consequences on children refugees, pushing them into labour market at an early age and young girls into early marriage. Moreover, Al-Haj et al, highlights that refugees are more susceptible to various types of injuries, including traumatic brain injury (TBI), due to the harsh living and working conditions that they endure [ 5 ]. Al Haj et al, found that the leading cause of these injuries among refugees in Lebanon were falls (44%) and violence (10%) [ 5 ].…”
mentioning
confidence: 99%
“…Moreover, Al-Haj et al, highlights that refugees are more susceptible to various types of injuries, including traumatic brain injury (TBI), due to the harsh living and working conditions that they endure [ 5 ]. Al Haj et al, found that the leading cause of these injuries among refugees in Lebanon were falls (44%) and violence (10%) [ 5 ]. The series also highlights the inequitable distribution of the COVID-19 vaccine in Lebanon.…”
mentioning
confidence: 99%